Determinan Kemiskinan di Kabupaten Pangkajene Kepulauan Tahun 2012-2021 - Sri Fatmasari Syam; Sapriyadi Sapriyadi (Universitas Batanghari Jambi, 2023)
The purpose of this study is to examine the effect of HDI, Economic Growth and Unemployment on Poverty in Pangkajene Islands Regency. The type of data to be analyzed in this research is secondary data in the form of time series data, namely entity data with time/period dimensions which in this study uses the 2012-2021 period. The analytical method used is a multiple linear statistical test modelor Ordinary Least Square (OLS). Through the SPSS Amos 26 software application. The results show that HDI has a negative and significant effect on Poverty, Economic Growth has no significant effect on Poverty, Unemployment has no significant effect on poverty.